Analysis of Digital Consumption Practices in Russian Regions Based on the Index Approach; Regional Research of Russia; Vol. 15, iss. 4 - Kashapova E. R. Elmira Ramisovna; Klemasheva E. I. Elena Igorevna; Malanina V. A. Veronika Anatolievna; Rozhdestvenskaya E. M. Elena Mikhailovna (2026, 2026)
Title screen